Gender equity and social inclusion in joint forest management: Lessons from two Indian states - Elias, Marlène (Bioversity International, 2017)
This brief focuses on gender equity and social inclusion in India’s Joint Forest Management (JFM) programme; one of the first and largest initiatives for collaborative forest governance worldwide. In JFM, the state, represented by the Forest Department (FD), and the village community share responsibilities and benefits of jointly protecting and managing forests adjoining villages. The agreement is operationalized through JFM Committees (JFMCs) – referred to as Village Forest Committees (VFCs) in some states – where elected community representatives and a FD official make forest-related decisions in a supposedly collaborative manner. In an effort to promote gender equity and social inclusion, seats are reserved on these committees for women and marginalized groups, such as Scheduled Castes (SCs) and Schedule Tribes (STs). Yet, despite reservations, the ability of these groups to actively engage in JFM processes remains limited.